Sterile and microbial-associated intra-amniotic inflammation in preterm prelabor rupture of membranes. (August 2015) - Romero, Roberto; Miranda, Jezid; Chaemsaithong, Piya; Chaiworapongsa, Tinnakorn; Kusanovic, Juan P.; Dong, Zhong; Ahmed, Ahmed I.; Shaman, Majid; Lannaman, Kia; Yoon, Bo Hyun; Hassan, Sonia S.; Kim, Chong Jai; et al.
Abstract Objective: The objectives of this study were to: (1) determine the amniotic fluid (AF) microbiology of patients with preterm prelabor rupture of membranes (PROM); and (2) examine the relationship between intra-amniotic inflammation with and without microorganisms (sterile inflammation) and adverse pregnancy outcomes in patients with preterm PROM. Methods: AF samples obtained from 59 women with preterm PROM were analyzed using cultivation techniques (for aerobic and anaerobic bacteria as well as genital mycoplasmas) and with broad-range polymerase chain reaction coupled with electrospray ionization mass spectrometry (PCR/ESI-MS). AF concentration of interleukin-6 (IL-6) was determined using ELISA. Results of both tests were correlated with AF IL-6 concentrations and the occurrence of adverse obstetrical/perinatal outcomes. Results: (1) PCR/ESI-MS, AF culture, and the combination of these two tests each identified microorganisms in 36% (21/59), 24% (14/59) and 41% (24/59) of women with preterm PROM, respectively; (2) the most frequent microorganisms found in the amniotic cavity were Sneathia species and Ureaplasma urealyticum; (3) the frequency of microbial-associated and sterile intra-amniotic inflammation was overall similar [ 29% (17/59)]: however, the prevalence of each differed according to the gestational age when PROM occurred; (4) the earlier the gestational age at preterm PROM, the higher the frequency of both microbial-associated and sterile intra-amniotic inflammation; (5) the intensity of the intra-amniotic inflammatory response against microorganisms is stronger when preterm PROM occurs early in pregnancy; and (6) the frequency of acute placental inflammation (histologic chorioamnionitis and/or funisitis) was significantly higher in patients with microbial-associated intra-amniotic inflammation than in those without intra-amniotic inflammation [93.3% (14/15) versus 38% (6/16); p = 0.001]. Conclusions: (1) The frequency of microorganisms in preterm PROM is 40% using both cultivation techniques and PCR/ESI-MS; (2) PCR/ESI-MS identified microorganisms in the AF of 50% more women with preterm PROM than AF culture; and (3) sterile intra-amniotic inflammation was present in 29% of these patients, and it was as or more common than microbial-associated intra-amniotic inflammation among those presenting after, but not before, 24 weeks of gestation.